PELATIHAN VISUALISASI DATA PADA DOKUMEN PERENCANAAN PEMBANGUNAN DAERAH MENGGUNAKAN MICROSOFT EXCEL - Farida Islamiah (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2024)
The purpose of data visualisation training on planning data at the Regional Development Planning Research and Development Agency (Bappedalitbang) of Paser Regency is to improve skills in operating Microsoft Excel applications to make data into graphs. The implementation time was on 28-30 December 2023 at the Paser Regency Bappedalitbang office. The results of this activity are that this activity has provided benefits and problem solutions from Bappedalitbang employees in presenting the planning data that has been compiled.